Optimizing the drying parameters of a fixed bed with reversing ventilation for peanut using computer simulation - Yan, Jianchun; Xie, Huanxiong; Wei, Hai; Wu, Huicang; You, Zhaoyan (International Journal of Agricultural and Biological Engineering, 2021)
To obtain the optimal operation parameters of fixed-bed reversing ventilation drying of peanuts, a set of partial differential equations indicating the heat and mass transfer relationships between the peanut pods and air during drying was proposed. Then, a series of discretized models were established for simulation, and the time consumed, unevenness, and energy consumption for batch drying were calculated. The results showed that reversing ventilation and segmented drying was helpful to these issues for high drying ability. The optimal operation parameters were determined by uniform design experimentation of mathematical simulation. The result showed that when the moisture content (wet basis) was above 22%, a ventilation velocity of 0.46 m/s was optimal; when the moisture content was between 8% and 22%, a ventilation velocity of 0.20 m/s was optimal. Using the optimal parameters, the computer simulating result was compared with the experimental results. The correlation coefficients between the simulating and the experimental values for the temperature and moisture content were all above 0.98 and the quality of dried peanuts was close to that of natural sun-dried ones, which indicates that the optimization results of the drying parameters are highly reliable.Keywords: peanut, fix bed drying, reversing ventilation, simulation, optimizationDOI: 10.25165/j.ijabe.20211405.6354Citation: Yan J C, Xie H X, Wei H, Wu H C, You Z Y. Optimizing the drying parameters of a fixed bed with reversing ventilation for peanut using computer simulation. Int J Agric & Biol Eng, 2021; 14(5): 255–266.